Pengaruh Gaya Kepemimpinan dan Budaya Organisasi Terhadap Komitmen Organisasi Dalam Meningkatkan Kinerja Pegawai pada Badan Perencanaan Pembangunan Daerah (Bappeda) Kabupaten Batang Hari - Nadiatul Khoiroh; Pantun Bukit; R Adisetiawan (J-MAS (Jurnal Manajemen dan Sains), 2019)
The Effect of Leadership Style and Organizational Culture on Organizational Commitment in Improving Employee Performance.This study examines the effect of Leadership Style and Organizational Culture on Organizational Commitment in Improving Employee Performance at Batang Hari Regency Development Planning Regency. The performance of employees is among the key issues are constantly faced by the organization management. Therefore, among the tasks of the manager is a very important move employees to contribute to the success of the organization.The purpose of this study is to examine and determine the effect of Leadership Style and Organizational Culture on Organizational Commitment in Improving Employee Performance tested either directly or indirectly.To examine issues directly above the survey conducted by distributing questionnaires to employees Batang Hari Regency Development Planning Regency. The results of the questionnaire were analyzed qualitatively and verification. Data analysis tool made by using Path Analysis.The results of this study indicate that the effect of Leadership Style and Organizational Culture on Organizational Commitment in Improving Employee Performanc have influence for employee performance, both directly and indirectly.